PLAYFUL SYSTEMATIC THEOLOGY: TOWARD TRANSFORMING ACTION - A. Stavnichuk (Acta Theologica)
This article demonstrates how re-imagining our understanding of the Holy Spirit in more comprehensive ways can be effective in moving Christians toward creative, transforming activities in the world. This article also provides some examples for undertaking systematic theology in a playful way by using the present ecumenical discourse of the World Council of Churches (WCC) on transforming spirituality.